Advanced Directions for the Financial Sovereignty Formation within the Framework of the Great Eurasian Partnership - V. Yu. Dodonov (Евразийская интеграция: экономика, право, политика, 2023)
The new conditions for the implementation of economic activity at the national and international levels require the accelerated formation of sovereignty in critical areas, one of which is financial. The formation of full-fledged financial sovereignty is relevant for all states of Greater Eurasia, and therefore it is advisable to implement this task through joint and coordinated efforts within the framework of a broad Eurasian partnership.Aim. Find out the most promising areas for the formation of financial sovereignty within the framework of a large Eurasian partnership.Methods. A comprehensive analysis of the causes and conditions for the dependence of national economies on external financial systems, a comparative analysis of the factors of Western components dominance in the global financial architecture.Results. The main directions of the formation of the financial sovereignty for the countries of Greater Eurasia on the basis of increasing the level of independence of national financial systems from the Western infrastructure of the financial sector are identified. The most promising methods for achieving this goal are proposed based on the creation of new types of reserve assets within the framework of a large Eurasian partnership, which are an alternative to debt obligations of the United States and European countries, as well as the formation of an integrated system for financial instruments trading by the countries of Greater Eurasia.Conclusions. The growing economic confront ation between the West and a number of the largest economies of Greater Eurasia is extremely relevant to the problem of the formation of real financial sovereignty, the achievement of which requires new approaches, the creation of a number of specialized institutions and large-scale cooperation between the leading economic centers of the continent in order to deepen the integration of national financial systems and markets.